THE ROLE OF PRESIDENT ABDEL FATTAH AL-SISI'S GOVERNMENT FOR THE DEVELOPMENT OF EGYPT'S POST-REVOLUTIONARY ECONOMIC REFORMS IN 2011 - Hardi Alunaza; Virginia Sherin (Arabic Literature Department, 2021)
After the revolution in 2011, Egypt has experienced various conditions of instability in various fields, especially the economy and politics. The government of Mohammed Morsi, which was previously expected improve the Egyptian economy, actually exacerbated the situation. The Egyptian people staged various protests and other forms of protest in order for the government to immediately improve the situation. However, the government failed to carry out conflict management so the military carried out a coup. Morsi's position was later replaced by Abdel Fattah Al-Sisi. Al-Sisi's background as a military figure led to repressive policies being implemented. During Al-Sisi's reign, there was a significant increase in the Egyptian economy. The purpose of this research is to identify the role of President Al-Sisi's government for the development of economic reform in Egypt after the 2011 Revolution. This research useda qualitative approach with an exploratory type of research, and refers to the theory of liberalism and the rational actor model. The results of this research indicate that President Al-Sisi's policies have a positive impact on the development of the Egyptian economy as indicated by an increase in Egypt's Gross Domestic Product, a decrease in inflation rates, and poverty.